Spiritual Entrepreneurship: An Approach to Understanding Christian Spirituality in Market Place - Hatta, Ignatius Bambang Sukarno; Lie, Romi (Sekolah Tinggi Teologi Simpson Ungaran, 2022)
Efforts to explore the spirituality of Christian work have become an urgent need, not because they want to compete with the spirituality of work that is currently going on in a secular manner, but as a form of fulfilling the Christian missionary call to